Harmonic analysis of a five level cascaded inverter under a new modulation scheme - Aziz, J.; Salam, Z. (Penerbit UTM Press, 2003)
This paper proposes an analytical method to predict the incidence and magnitude of harmonics of the output voltage of a five-level cascaded inverter. The cascaded inverter is subjected to a new modulation scheme, which uses multiple modulating signals with a single carrier. From the modulation scheme, mathematical equations that define the PWM switching instants are derived. In order to justify the merits of the proposed modulation scheme, harmonic analysis for the Fourier coefficients is outlined and calculated using MATLAB. An experimental five-level cascaded inverter test-rig is built and the new modulation scheme is implemented. The calculated and measured harmonics of the output voltage are compared and discussed.